Analysis of problems and challenges in the legislation of the Republic of Kazakhstan on personal data protection and international legal regulation - Iskakova, Zh.T.; Kadyrzhanova, T.S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The authors analyze the international legal and national legal regulation in order to study, determine the level of regulatory security of identification and authentication of individuals and legal entities for the purpose of their legally significant actions in various areas of public relations in the Republic of Kazakhstan. The authors have attempted to formulate certain conclusions and proposals. On the one hand, these formulated recommendations will enable the state to ensure the level of trust of citizens and legal entities in the field of electronic information interaction. On the other hand, the same proposals will reduce the risks associated with leaks of biometric databases of users of information systems, and contribute to maintaining the confidentiality of biometric personal data of individuals and legal entities. As well as the recommendations aim at improving efficiency in the field of publiclegal and private-legal relationships carried out through electronic services.